2012
DOI: 10.1007/s11999-012-2317-4
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Formulation Increases Local Delivery of Amphotericin from Bone Cement: A Pilot Study

Abstract: Background Amphotericin is a highly toxic hydrophobic antifungal. Delivery of amphotericin from antifungalloaded bone cement (ALBC) is much lower than would be expected for an equivalent load of water-soluble antibacterials. Lipid formulations have been developed to decrease amphotericin toxicity. It is unknown how lipid formulations affect amphotericin release and compressive strength of amphotericin ALBC. Questions/purposes We asked if amphotericin release from liposomal amphotericin ALBC (1) changed with am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 10 publications
5
41
1
Order By: Relevance
“…This report confirms the activity of delivered voriconazole at all collection time points, verifying that active voriconazole is delivered from the cement. Recent work in our laboratory has confirmed the activity of both liposomal and deoxycholate formulations of amphotericin B eluted from bone cement [2].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This report confirms the activity of delivered voriconazole at all collection time points, verifying that active voriconazole is delivered from the cement. Recent work in our laboratory has confirmed the activity of both liposomal and deoxycholate formulations of amphotericin B eluted from bone cement [2].…”
Section: Discussionmentioning
confidence: 71%
“…Various studies describe surgeon-directed antifungal formulations of antimicrobial-loaded bone cement (ALBC) [2,6,9,10,15,16]. Published data from amphotericin B studies establish limited release occurs, increased release using the liposome formulation, higher than expected compressive strength, possibly related to crosslinking with PMMA, and cytotoxicity at low concentrations [2,5,8,9]. However, clinical experience in a case report by Marra et al [10] suggests that sufficient amphotericin B is released in vivo to be measurable and clinically efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity from amphotericin B from the deoxycholate formulation occurred at lower concentrations than from the liposomal formulation. The phospholipid in the liposomal formulation of amphotericin B leads to higher release from ALBC but likely also reduces toxicity through the formation of liposomes, limiting exposure to free drug [4]. After removal of amphotericin B from the growth media, cells that were exposed to these sublethal concentrations increased their numbers over 3 days [6].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously studied ALBC with amphotericin B deoxycholate [8], finding limited release and significant toxicity to fibroblasts and osteoblasts at relatively low concentrations [6]. We subsequently showed that both liposomal amphotericin B [4] and voriconazole [12] are delivered from ALBC in much greater amounts than amphotericin B deoxycholate. Liposomal amphotericin B is known to be less toxic than amphotericin B deoxycholate when delivered intravenously [2]; however, there are no reported data on the local toxicity from locally delivered liposomal amphotericin B.…”
Section: All Icmje Conflict Of Interest Forms For Authors and Clinicamentioning
confidence: 99%
“…In an effort to determine the important parameters for effective local delivery, many authors have studied antimicrobial elution in vitro [8,18,19]. Elution studies evaluate the delivery vehicle's maximum capability to release antimicrobial, often inappropriately comparing eluant concentrations to the minimum inhibitory concentration (MIC) of target organisms.…”
Section: Introductionmentioning
confidence: 99%